Estudo da alimentação de sólidos em sistemas de transporte pneumático - Lopes, Cibele Souza (Universidade Federal de São Carlos, 2011)
One of the most important parts in a pneumatic conveying is the solids feeding system due its complexity fluid dynamic, besides affecting the operational stability, economical and technical feasibility and system efficiency. The purpose of this wok was to carry out a experimental study of fluid dynamic of feeding configuration for different operational conditions, made of non-mechanicals devices and reduction nozzle combinations, considering the influence in all pneumatic conveying system. The feeders applied were inclined pipe and L-valve, with and without reduction nozzle. Moreover, the spouted bed and the horizontal feeders were analyzed as well, which on their original design has reduction area for the flow. An analyses and a comparison of the fluid dynamic data obtained for feeding configurations in a pneumatic loop with 53,4 mm of internal diameter tube and transporting 1 mm glass spheres showed a relationship between the operational conditions and the type of feeder, resulting in air velocity and solid flow rate characteristics for each case . This study also gives the idea to apply reductions nozzles combined with non-mechanicals solid feeder in order to increase the solid flow rate. Up to the moment, the reduction nozzle was indicated just to get better the operation stability.
Keywords: Engenharia química; Fenômenos de transporte; Transporte por tubo pneumático; Fluidodinâmica; Alimentador de sólidos; Alimentadores não-mecânicos; ENGENHARIAS::ENGENHARIA QUIMICA